2022
DOI: 10.31223/x51c8j
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of satellite precipitation products for water allocation studies in the Sio-Malaba-Malakisi River Basin of East Africa

Abstract: throughout the basin. At lower altitudes, the products overestimated rainfall events as indicated by the performance measures. The COSERO results indicate that PERSIANN-CDR and MSWEPv2.2 overcompensated and underestimated discharge throughout the basin. This could be attributed to differences in temporal dynamics of the products. In overall, seasonal trends captured by the SPPs can be used to support catchment management efforts in data scarce regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…It remains important to benchmark remote sensing or numerical modelling-based rainfall products like CHIRPS or meteorological parameters from ERA5L. Although many issues exist regarding comparability of products covering very different spatial domains (Omonge et al, 2021), a comparison simply helps to gain credibility and assurance. The estimates of AET are purely model driven and could not be validated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains important to benchmark remote sensing or numerical modelling-based rainfall products like CHIRPS or meteorological parameters from ERA5L. Although many issues exist regarding comparability of products covering very different spatial domains (Omonge et al, 2021), a comparison simply helps to gain credibility and assurance. The estimates of AET are purely model driven and could not be validated.…”
Section: Discussionmentioning
confidence: 99%
“…Our decision to use CHIRPS is based on several studies applying CHIRPS in East Africa, which showed comparatively better performances and agreements of CHIRPS with station data (e.g. Dinku et al, 2018Dinku et al, , 2007Kimani et al, 2017;Omonge et al, 2021). Also, recently Kimaru et al, (2019) modelled the inflows to Lake Nakuru using CHIRPS rainfall as input.…”
Section: Rainfall Datamentioning
confidence: 99%